Anthropometric characteristics and somatotype of professional soccer players by position - Cavia, M. M.; Moreno, A.; Fernández-Trabanco, B.; Carrillo, C.; Alonso-Torre, S. R. (Journal of Sports Medicine and Therapy, 2019)
This is an open access article distributed under the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly citedKeywords:Anthropometry; Body fat; Skinfolds; Soccer; SomatotypeIntroductionFootball is the most popular and played sport in the world and during the last decades a number of research has focused on studying the factors that inßluence the performance of a player [1-4]. Some studies conclude that there is a close relation between the anthropometric and the physiologic characteristics of the player and its ability to play football at a certain level [1,5,6]; such characteristics are decisive for an optimal physical leveland therefore a good level in the game [4,7,8]. These researches aim to ßind the ideal football player: how his body composition, somatotype, training, diet or rest shouldAbstract The anthropometric characteristics are decisive for an optimal physical level and, therefore, a good level in the game; and they can be different depending on the game position. The aim of this study was to identify the physical characteristics, body composition and somatotype of professional soccer players and to verify differences according to their playing positions: goalkeepers, defenders, forwards and midfi elders. The measurements were performed on 57 male players of a soccer team of the Spanish Football League One. Twenty seven anthropometric variables were measured (height and body weight, four bone breadths, eleven girths and ten skinfolds) and the Bioelectrical Impedance Analysis was also performed. The percentage of body fat has been determined from 11 different equations.Goalkeepers showed the highest weight (80.2 ± 3.2 kg), supraespinal (10.5 ± 3.8 mm) and abdominal (15.6 ± 3.5 mm) skinfolds than others positions. In relation to body fat percentages, similar results were obtained from the equations of Jackson-Pollock (from 3 and 7 skinfolds), Carter, Withers, and Heyward and Stolarczyk (mean value 7.8 ± 1.5%). Higher results were obtained from the other equations applied. Differences among positions were also found concerning body composition; goalkeepers showed the highest body fat percentage (9.4 ± 1.4%). Mean somatotype was also different among positions; goalkeepers and forwards presented a balanced mesomorph somatotype while defenders and midfi elders showed an ecto-mesomorph one.The differences in morphological characteristics according to the team position were notice only in goalkeepers, especially regarding their weight, abdominal and supraespinale skinfolds and the percentage of fat tissue.